2015
DOI: 10.1109/msp.2014.2359131
|View full text |Cite
|
Sign up to set email alerts
|

Signal Processing Challenges in Quantitative 3-D Cell Morphology: More than meets the eye

Abstract: International audienceModern developments in light microscopy have allowed the observation of cell deformation with remarkable spatiotemporal resolution and reproducibility. Analyzing such phenomena is of particular interest for the signal processing and computer vision communities due to the numerous computational challenges involved, from image acquisition all the way to shape analysis and pattern recognition and interpretation. This article aims at providing an up-to-date overview of the problems, solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…3) Discussion and Perspectives: A number of pioneering studies in cell shape classification [278]- [281] based on the previous approaches have opened up the way to start and connect phenomenological features like the structure of blebs, the dynamics of the subcortical cytoskeleton and its links to membrane during protrusion to the underlying molecular mechanisms that determine and regulate them. They represent also a first step towards understanding how cells generate force for shape change and movement and how they respond to mechanical force stimuli.…”
Section: ) Cell Tracking Methodsmentioning
confidence: 99%
“…3) Discussion and Perspectives: A number of pioneering studies in cell shape classification [278]- [281] based on the previous approaches have opened up the way to start and connect phenomenological features like the structure of blebs, the dynamics of the subcortical cytoskeleton and its links to membrane during protrusion to the underlying molecular mechanisms that determine and regulate them. They represent also a first step towards understanding how cells generate force for shape change and movement and how they respond to mechanical force stimuli.…”
Section: ) Cell Tracking Methodsmentioning
confidence: 99%
“…MM, a nonlinear analysis method based on signal processing in time domain, is excellent in noise removal and fast calculation [4]. MM is mainly applied to extract specific features in the neighborhood of every sample in the signal under analysis [5].…”
Section: Ntroductionmentioning
confidence: 99%
“…While efforts have been made to develop cell and nuclear shape characteristics in 2D or pseudo-3D 11,12 , several studies have demonstrated that 3D morphometric measures provide better results for nuclear shape description and discrimination [13][14][15] . However, 3D shape descriptors that permit robust morphological analysis and facilitate human interpretation are still under active investigation 16 . Additionally, the dimensionality and volume of acquired data, various image acquisition conditions, and great variability of cell shapes in a population present challenges for 3D shape analysis methods that should be scalable, robust to noise, and specific enough across cell populations at the same time.…”
Section: Introduction Motivationmentioning
confidence: 99%